Стихотворения - Бунин Иван Алексеевич (Библиотека "ХХ век: поэт и время", 1990)
Экземпляры: ф.10 (1991) / Инвентарный номер: 33557 / Цена: / Сис.шифр: 84(2Рос=Рус)1-5 / Авт.знак: Б 91 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)1-5